Food Quality, Territory And Symbols: What Do Geographical Indications Certify? (Sociologia del diritto, 2024)
European legislation on food quality provides for two levels of standards: health safety, and organic and geographical quality. The regulation on quality schemes does not define common quality criteria but protects a presupposed uniqueness of foods justified by territory, tradition, and organoleptic properties. Through the analysis of seven product specifications, this article aims to discuss whether the territory of origin and the organoleptic properties of foods are sufficient criteria to define food quality and whether the link to the territory is a sufficient criterion to consider geographical indications as environmentally sustainable production. Socio-legal research needs to examine, on the one hand, the categories of certified foods and the production systems in which they are found; on the other hand, whether the certification symbols enable consumers to recognize products of superior quality.
Keywords: food quality; sustainability; geographical indications